Risk of venous thromboembolism associated with single and combined effects of Factor V Leiden, Prothrombin 20210A and Methylenetethraydrofolate reductase C677T: a meta-analysis involving over 11,000 cases and 21,000 controls (2013)
ABSTRACT: BACKGROUND—Genetic and environmental factors interact in determining the risk of venous thromboembolism (VTE). The risk associated with the polymorphic variants G1691A of factor V (Factor V Leiden,FVL), G20210A of prothrombin (PT20210A) and C677T of methylentetrahydrofolate reductase (C677T MTHFR) genes has been investigated in many studies. METHODS—We performed a pooled analysis of case-control and cohort studies investigating in adults the association between each variant and VTE, published on Pubmed, Embase or Google through January 2010. Authors of eligible papers, were invited to provide all available individual data for the pooling. The Odds Ratio (OR) for first VTE associated with each variant, individually and combined with the others, were calculated with a random effect model, in heterozygotes and homozygotes (dominant model for FVL and PT20210A; recessive for C677T MTHFR). RESULTS—We analysed 31 databases, including 11,239 cases and 21,521 controls. No significant association with VTE was found for homozygous C677T MTHFR (OR: 1.38; 95% confidence intervals [CI]: 0.98–1.93), whereas the risk was increased in carriers of either heterozygous FVL or PT20210 (OR=4.22; 95% CI: 3.35–5.32; and OR=2.79;95% CI: 2.25–3.46, respectively), in double hterozygotes (OR=3.42; 95%CI 1.64-7.13), and in homozygous FVL or PT20210A (OR=11.45; 95%CI: 6.79-19.29; and OR: 2.79; 95%CI: 2.25 – 3.46, respectively). The stratified analyses showed a stronger effect of FVL on individuals ≤45 years (p-value for interaction = 0.036) and of PT20210A in women using oral contraceptives (p-value for interaction = 0.045). CONCLUSIONS—In this large pooled analysis, inclusive of large studies like MEGA, no effect was found for C677T MTHFR on VTE; FVL and PT20210A were confirmed to be moderate risk factors. Notably, double carriers of the two genetic variants produced an impact on VTE risk significantly increased but weaker than previously thought.